KETIKA PEGAWAI TAK LAGI PEDULI: MENELUSURI AKAR APATISME PEGAWAI DI LEMBAGA PENDIDIKAN TINGGI - Kurniawan, Ade; Suroto, Suroto; Andhika, M. Rezki (Program Studi Manajemen Pendidikan Islam, 2025)
Employee apathy within higher education institutions poses a significant challenge to the development of a healthy and productive organizational culture. This article aims to explore the root causes of apathetic attitudes among academic staff and propose relevant mitigation strategies. Employing a narrative literature review approach, this study synthesizes key findings related to disengagement, leadership, reward systems, workload, and organizational culture. The findings reveal that apathy is not merely an individual issue, but rather reflects structural failures in providing a fair, supportive, and inclusive work environment. Key contributing factors include uninspiring and exclusive leadership, unfair performance evaluations, excessive workloads without sufficient support, and authoritarian, non-humanistic organizational cultures. To address these issues, a holistic strategy is required, encompassing visionary leadership, transparent and fair reward systems, enhanced organizational support, and cultural transformation toward humanistic and collaborative values. This article serves as a conceptual reference for higher education leaders seeking to create a more participatory, healthy, and sustainable work climate.